Perbandingan Face Recognition dan QR Code Dalam Sistem Absensi Menggunakan Geolocation Berbasis Mobile - Suniantara, I Gusti Ngurah Gede Agung; Linawati, Linawati; Manuaba, Ida Bagus Gede (Jurnal Teknologi Elektro; Vol 21 No 1 (2022): ( Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2022.v21i01.P11, 2022)
Abstract— The development of increasingly sophisticated technology makes mobile devices become main alternative in managing life's affairs. Mobile device that offers services and computing is a smartphone. The sophistication of smartphone technology can be used to process attendance. Attendance system is a system that can record presence of each user, attendance system can be processed using several types of attendance including conventional attendance using a signature and digital attendance using Face Recognition and QR code. Processing attendance system, the geolocation feature can be used to find location. This study aims to explain and determine the best digital attendance method between Face Recognition and QR code using geolocation. Based on the explanation of previous research and comparing the Face Recognition and QR code methods in processing the attendance system, the results obtained that the QR code method is the best method for digital attendance because it has high accuracy and is easier to implement. Key Words— Attendance System, Mobile Device, Geolocation, Face Recognition, QR code